Effect of Inulin and Auricularia polytricha Extract on Proliferation of Lactobacillus rhamnosus - Gulcin Alp Avci; Burcin Ozcelik; Ceren Kesepara (Hittite Journal of Science and Engineering, 2017)
Probiotic microorganisms have many health-beneficial effects on gastrointestinal system and their therapeutic usage is becoming increasingly common in human and veterinary medicine. Many different species and strains of bacteria, yeast and even fungi have been extensively used as potential probiotics. Among the probiotic strains, Lactobacillus rhamnosus is one of the most commonly used strain for probiotic treatment and health promoting functions of this strain are well documented. To enhance therapeutic effects of probiotics, prebiotics have been extensively used. Prebiotics stimulate the proliferation of probiotics and this may have positive effects on the maintenance of the balance between pathogenic and nonpathogenic bacteria. In this study, we aimed to evaluate the effect of inulin and Auricularia polytricha aqueous extract on the proliferation of L. rhamnosus. For this purpose, L. rhamnosus was inoculated in three different MRS broth supplemented with inulin 5%, A. polytricha extract 5% and with the mixture of inulin 5% plus A. polytricha extract 5%. Our results indicated that L. rhamnosus was able to use inulin and fungus extract as a carbon source. Moreover,combined use of inulin and A. polytricha improved prebiotic efficacy